Coenzyme Q10 Supplementation and Oocyte Aneuploidy in Women Undergoing IVF-ICSI Treatment - Yaakov Bentov; Thomas Hannam; Andrea Jurisicova; Navid Esfandiari; Robert F. Casper (SAGE Publishing, 2014)
Background The age-related reduction in live-birth rate is attributed to a high rate of aneuploidy and follicle depletion. We showed in an animal model that treatment with Coenzyme Q10 (CoQ10) markedly improved reproductive outcome. The aim of this study was to compare the post-meiotic oocyte aneuploidy rate in in vitro fertilization (IVF) and intra cytoplasmic sperm injection (ICSI) patients treated with CoQ10 or placebo. Methods We conducted a double blind placebo controlled randomized trial that included IVF-ICSI patients 35-43 years of age. The patients were treated with either 600 mg of CoQ10 or an equivalent number of placebo caps. We compared the post-meiotic aneuploidy rate using polar body biopsy (PBBX) and comparative genomic hybridization (CGH). According to the power calculation, 27 patients were needed for each arm. Results Owing to safety concerns regarding the effects of polar body biopsy on embryo quality and implantation, the study was terminated before reaching the target number of participants. A total of 39 patients were evaluated and randomized (17 CoQ10, 22 placebo), 27 were given the study medication (12 CoQ10, 15 placebo), and 24 completed an IVF-ICSI cycle including PBBX and embryo transfer (10 CoQ10, 14 placebo). Average age, base line follicle stimulating hormone (FSH), peak estradiol and progesterone serum level, as well as the total number of human menopausal gonadotropin (hMG) units--did not differ between the groups. The rate of aneuploidy was 46.5% in the CoQ10 group compared to 62.8% in the control. Clinical pregnancy rate was 33% for the CoQ10 group and 26.7% for the control group. Conclusion No significant differences in outcome were detected between the CoQ10 and placebo groups. However, the final study was underpowered to detect a difference in the rate of aneuploidy.